Technical features of the botanical ornaments on the carpet in the Al-Abbasiyah Holy Shrine Museum (Journal of the College of Basic Education, 2022)
Muslim world has witnessed creative peerless art of ornaments and especially botanical ornaments, as it enabled the plant ornaments give formative character, through creations of Muslim artist and influenced by social reality experienced as well as religious environment. The result these circumstance were imposed a positive impact on his personality, led to the flourishing of arts , crafts and ornament formed an extension of the age of the intellectual and cultural prosperity and close association with the phenomenon of Islamic revival. From here the ornaments were regarded one of the great Islamic art that has a clear impact on the decorating materials with its multi-uses, both in buildings and mosques or carpet. And the fact that research highlights the technical features of botanical ornaments on the carpet in the Al-Abbasiyah Holy Shrine Museum I considered to be studied according to the perspectives of art and creative and systematic scientific determined through the first chapter , which included the problem of the research and its importance as well as its objectives, which summed up the researcher with a number of points the most important disclosure of diversity formal and technical botanical ornaments in the kept carpet design in the Al-Abbasiyah Holy Shrine Museum as well as the limits of research and determine the terminology, but the second chapter deal with theoretical framework and previous studies.the researchers also touch upon a number of vocabularies within the content of the theoretical framework included a historical introduction and detection technical diversity and the formal trappings of the carpet. Third chapter included research methodology through the research community and specimens and number as well as the way in which researchers analyzed will be followed to get to the results several conclusions in the fourth chapter in order to achieve scientific objective and purpose of the study.